Gender differences in the usage of ICT (Information Communication Technology) among employees in Sabah Immigration Department (Jabatan Imigresen Sabah) / Hishamudin Badiyol Zuman - Zuman, Hishamudin Badiyol (2007)
This paper, presents findings of a study that was carried out in April 2009 at the Department of Immigration Kota Kinabalu to determine gender differences in the usage of ICT (Information Communication Technology) among employees in Kota Kinabalu Sabah Immigration Department. 150 employees were surveyed of which 81 were females while 69 were male. The population of employees at Kota Kinabalu Immigration is 857. Systematic random sampling was used to select respondents from the six unit of the Department; a survey questionnaire was administered to them and collected on its completion. Descriptive statistics, t-test, crosstabulation and chi Square were used in the analysis of data. The results suggest that gender differences exist between female and male employees at the Kota Kinabalu Sabah Immigration Department with regard to the usage of ICT. The findings further revealed that there are factors associated with the usage of the ICT among employees in the Kota Kinabalu Sabah Immigration Department.